Bio-Inspired Microwave Modulator for High-Temperature Electromagnetic Protection, Infrared Stealth and Operating Temperature Monitoring - Yang, Xuan; Duan, Yuping; Li, Shuqing; Pang, Huifang; Huang, Lingxi; Fu, Yuanyuan; Wang, Tongmin (Nano-Micro Letters, 2021)
High-temperature electromagnetic (EM) protection materials integrated of multiple EM protection mechanisms and functions are regarded as desirable candidates for solving EM interference over a wide temperature range. In this work, a novel microwave modulator is fabricated by introducing carbonyl iron particles (CIP)/resin into channels of carbonized wood (C-wood). Innovatively, the spaced arrangement of two microwave absorbents not only achieves a synergistic enhancement of magnetic and dielectric losses, but also breaks the translational invariance of EM characteristics in the horizontal direction to obtain multiple phase discontinuities in the frequency range of 8.2–18.0 GHz achieving modulation of reflected wave radiation direction. Accordingly, CIP/C-wood microwave modulator demonstrates the maximum effective bandwidth of 5.2 GHz and the maximum EM protection efficiency over 97% with a thickness of only 1.5 mm in the temperature range 298–673 K. Besides, CIP/C-wood microwave modulator shows stable and low thermal conductivities, as well as monotonic electrical conductivity-temperature characteristics, therefore it can also achieve thermal infrared stealth and working temperature monitoring in wide temperature ranges. This work provides an inspiration for the design of high-temperature EM protection materials with multiple EM protection mechanisms and functions. Highlights: 1 A multifunctional microwave modulator is developed for electromagnetic protection, infrared stealth and operating temperature monitoring over wide temperature ranges for the first time. 2 Microwave modulator achieves the integration of two electromagnetic protection mechanisms, microwave absorption and radiation deflection. 3 Microwave modulator demonstrates the maximum effective bandwidth of 5.2 GHz with a thickness of only 1.5 mm in the temperature range 298–673 K.